Energetic disorder dominates optical properties and recombination dynamics in tin-lead perovskite nanocrystals - Dandan Wang; Yusheng Li; Yongge Yang; Chao Ding; Yuyao Wei; Dong Liu; Hua Li; Huan Bi; Shikai Chen; Sujun Ji; Boyu Zhang; Yao Guo; et al. (eScience)
Tin-lead alloyed perovskite nanocrystals (PNCs) offer a promising pathway toward low-toxicity and air-stable light-emitting devices. However, substantial energetic disorder has thus far hindered their lighting applications compared to pure lead-based PNCs. A fundamental understanding of this disorder and its impact on optical properties is crucial for overcoming this limitation. Here, using temperature-dependent static and transient absorption spectroscopy, we meticulously distinguish the contributions of static disorder (including defects, impurities, etc.) and dynamic disorder (carrier–phonon interactions). We reveal how these disorders shape band-tail structure and ultimately influence inter-band carrier recombination behaviors. Surprisingly, we find that static and dynamic disorder primarily control band-tail defect states and bandgap renormalization, respectively, which together modulate fast carrier trapping and slow band-band recombination rates. Furthermore, we link these disorders to the tin-induced symmetry-lowering distortions in tin-lead alloyed PNCs. These findings illuminate critical design principles for highly luminescent, low-toxicity tin-lead PNCs, accelerating their adoption in optoelectronic applications.